Pengaruh Pembelajaran Teaching Factory Dengan Minat Berwirausaha Siswa di SMK Negeri 3 Palembang - Syahdita, Athirah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Vocational school education aims to change the mindset of graduates so they are ready to work and become independent entrepreneurs. Increasing the potential of vocational school graduate students is considered not optimal because many are not yet entrepreneurs. This can be seen from the failure of the soft skills improvement program in vocational schools. Steps that can be taken are to apply learning that focuses on real industries such as the Teaching Factory. So, the aim of this research is to determine the influence of Teaching Factory learning on students' entrepreneurial interest at SMK Negeri 3 Palembang. This research uses a quantitative descriptive approach. Based on research results, implementing the Teaching Factory Learning Model will influence students' entrepreneurial interest. This is shown by the value of the Teaching Factory Learning regression coefficient (X), which is 2.125, which is positive, and t-count is 10.810 > t-table 1.996 with a significant level of 0.000 < 0.05, so H0 is rejected, meaning H1 acceptance and interest in entrepreneurship are influenced by the Teaching learning model. Factory amounted to 63.3%.